2022
DOI: 10.3390/ijms23115976
|View full text |Cite
|
Sign up to set email alerts
|

Does Trophectoderm Mitochondrial DNA Content Affect Embryo Developmental and Implantation Potential?

Abstract: A retrospective case control study was undertaken at the molecular biology department of a private center for reproductive medicine in order to determine whether any correlation exists between the mitochondrial DNA (mtDNA) content of trophectoderm and embryo developmental potential. A total of 275 couples underwent IVF treatment, producing a total of 716 embryos. The trophectoderm was biopsied from each embryo at the blastocyst stage (day 5 or day 6 post-fertilization) subjected to low-pass next-generation seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Victor and coworkers [70] were unable to find a relationship between mtDNA content and clinical outcomes in euploid embryos. Likewise, other studies did not identify any implantation benefits in embryos with reduced mtDNA content [71][72][73]. Moreover, the analysis of TE samples from 615 euploid human blastocysts showed that mtDNA content was not predictive of euploid human embryo reproductive competence [74].…”
Section: Molecular Markers Of Embryo Qualitymentioning
confidence: 93%
“…Victor and coworkers [70] were unable to find a relationship between mtDNA content and clinical outcomes in euploid embryos. Likewise, other studies did not identify any implantation benefits in embryos with reduced mtDNA content [71][72][73]. Moreover, the analysis of TE samples from 615 euploid human blastocysts showed that mtDNA content was not predictive of euploid human embryo reproductive competence [74].…”
Section: Molecular Markers Of Embryo Qualitymentioning
confidence: 93%
“…Practically, the assessment of mtDNA quantity accompanying the preimplantation genetic testing for aneuploidy (PGT-A) of the trophectoderm biopsy has been used to predict embryo implantation potential. Studies in multiple clinics found that high mtDNA levels in blastocysts were related to aneuploidy embryos and implantation failure ( 216 218 ). The latest retrospective investigation analyzed the transfer cycle of frozen single euploid embryos, and the results showed that no correlation was observed between mtDNA content and blastocyst morphology grades or pregnancy outcomes ( 219 , 220 ).…”
Section: Focus On Mitochondria Of Human Oocyte During Assisted Reprod...mentioning
confidence: 99%
“…Still, lower mtDNA content was associated with delayed blastocyst development ( 219 ). It should be noted that there is currently no consensus on the threshold for the mtDNA copy number of blastocysts, and the accuracy of using mtDNA copy number as a single predictive biomarker for embryo selection and developmental potential remains low ( 216 220 ).…”
Section: Focus On Mitochondria Of Human Oocyte During Assisted Reprod...mentioning
confidence: 99%
“…In human blastocysts with mtDNA copy number exceeding an established threshold, this ominous sign forecasts poor reproductive outcome [ 51 , 52 ]. For example, mtDNA copy number is much higher for aneuploid embryos [ 53 ], illustrating a ‘less is more’ relation for human embryos and mtDNA copy number [ 54 , 55 ]. Further IVF experience with human embryo culture has indeed shown how mtDNA levels are usually far lower for cases with successful live birth [ 56 ].…”
Section: Subcellular Characteristics After Prpmentioning
confidence: 99%